SOVIET SLICE OF LIFE IN THE SECOND HALF OF XX CENTURY ON MATERIALS OF STAVROPOL NOTARIES - Alexey V. Dolgov (Вестник Северо-Кавказского федерального университета)
In article property, economic, social and other manifestations vital the practician of the population of Stavropol Krai in the 1960th - the 1980th years reflected in notarial documents are considered.